2009
DOI: 10.1007/s10562-009-0062-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Sulfonated Porous Carbon Catalyst with High Specific Surface Area

Abstract: A sulfonated (SO 3 H-bearing) carbon catalyst with mesoporous structure and high specific surface area is successfully prepared by impregnating the cellulosic precursor (wood powder) with ZnCl 2 prior to activation and sulfonation. The specific surface area of the porous carbon catalyst thus prepared is also found to increase with carbonization temperature to a maximum of 1,560 m 2 g -1 at ca. 773 K. Structural analyses reveal that the porous carbon catalysts carbonized at temperatures higher than 723 K contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
128
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(133 citation statements)
references
References 23 publications
4
128
0
1
Order By: Relevance
“…The development of solid acid catalyst based on metal oxides receives attention in as much as other solid materials such as ion-exchange resin, heteropolyacids, zeolite, carbon mesopore and modified clay [1][2][3][4][5][6][7][8]. Taking economically aspect and ease of synthesis as consideration, metal oxides might the best option to obtain heterogeneous catalyst with strong acidity and good thermal resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The development of solid acid catalyst based on metal oxides receives attention in as much as other solid materials such as ion-exchange resin, heteropolyacids, zeolite, carbon mesopore and modified clay [1][2][3][4][5][6][7][8]. Taking economically aspect and ease of synthesis as consideration, metal oxides might the best option to obtain heterogeneous catalyst with strong acidity and good thermal resistance.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of biomass-derived sulfonated carbon materials bearing SO3H, COOH, and phenolic OH groups (Kitano et al 2009;Kastner et al 2012) have been prepared via the similar route first reported by the Hara group (Hara et al 2004;Toda et al 2005;Nakajima et al 2007), i.e., natural organic resources are initially incompletely carbonized to obtain amorphous carbon and then subjected to sulfonation to introduce SO3H groups. These kinds of catalysts are efficient in the catalytic production of HMF, e.g., sulfonated cellulose-derived carbon, prepared by the incomplete carbonization of cellulose at 400 °C, followed by sulfonation with concentrated sulfuric acid (98%) at 180 °C (10 mL acid¡g -1 carbon) for 5 h. This process achieved 81.4% and 46.4% yields of HMF in ionic liquid 1-butyl-3-methylimidazolium chloride ([BMIM]Cl) from fructose and glucose, respectively (Hu et al 2013), and sulfonated corn stalk-derived carbon achieved 44.1% HMF yield from corn stalk in [BMIM]Cl (Yan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Among carbon-based materials, those functionalized with sulfonic acid groups have been investigated as potential, environment-friendly solid-acid catalysts, because functionalized carbons eliminate the need for liquid acids in several catalytic reactions, and may be reused several times without appreciable loss of activity [11]. Among acidic carbons, those obtained from waste materials and/or sugars are economically and environmentally attractive.…”
Section: Introductionmentioning
confidence: 99%